Upaya Mengurangi Rendahnya Minat Literasi pada Siswa Kelas 6 SDN Plerean 2 Kabupaten Jember - Mutmainnah, Mutmainnah; Agustin, Erninda Puji; Setianto, Bayu; Balya, Dhanial; Allam, Daffa` Abiyyu Sulthan; Daniaturrohman, Fida; Wardana, Hengky; Meylani, Dian; Mahbubah, Zaitun; Arifin, Irman; Sunarko, Viandra Rafelia Cahya; Rohman, Irsyad Zaki; Laily, Faikhatul; Ramadani, Fitria Ayu; Kurniawati, Nani (Kreativasi : Journal of Community Empowerment, 2024)
The "Melek Literasi" work program began on August 3, 2024, in SDN Plerean 2 in Sumberjambe District. The goal of this study was to improve grade 6 students' interest in reading literacy at SDN Plerean 2, Sumberjambe District. This work program is intended to promote the formation of a literacy culture at a young age, with a particular focus on grade 6 children who will shortly continue their education to a higher level, namely Junior High School. The primary material utilised in this program is micro fiction novels, which are meant to develop interest in reading literacy among grade 6 pupils. This work program began with a site study and collaboration with teachers and the administrator of SDN Plerean 2 in Sumberjambe District. Of the 28 pupils in Class 6 of SDN 2 Plerean, 26 said they were motivated to read more. The work program of the Jember Collaborative KKN students at Posko 205 in Plerean Village is projected to help reduce oscillations in reading interest rates in Indonesia and enhance the accomplishment of national literacy objectives.